Recycling of thermoplastic polystyrene waste using citrus peel extract for oil spill remediation. Issue 33 (29th April 2019) - Yadav, Shital; Mattaparthi, Srinadh; Sreenivasulu, Kuncham; Khandelwal, Mudrika; Majumdar, Saptarshi; Sharma, Chandra Shekhar
ABSTRACT: In this work, we report a low‐cost, less energy intensive, and an innovative way of recycling thermoplastic polystyrene (PS) waste objects into submicron, aligned fibers using extract from citrus peel, an agricultural waste. As‐fabricated recycled PS fabric is then structurally characterized and tested as an oil sorbent material. The hydrophobic‐oleophilic PS fabric is found to absorb 40.5 ± 3.6 g/g of oil, with 77.3% oil retention within 1 h. To investigate the practical application of recycled PS fabric for oil spills remediation, we tested its buoyancy properties in oil‐over‐water static and dynamic system besides examining their reusability. The as‐fabricated fabric floats on water after oil sorption indicating its high buoyancy and therefore can be collected easily after soaking the oil. This work is a simple illustration of systematic analysis of recycling two different waste materials (thermoplastic polystyrene and citrus peels) and reusing them into a more valuable product. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47886. Abstract : A hydrophobic and oleophilic recycled polystyrene fabric for oil spills remediation